Linking Person Job Fit, Person Organization Fit and Organizational Culture to Employee Performance in Islamic Banks: the Mediating Role of Job Motivation - Windy Delvyana Wulandari (Journal of Islamic Economic and Business Research, 2021)
Adaptability to the work environment affects employee's work attitude in the organization. This ability can be seen from the influence of person job fit, person organization fit, and organizational culture accumulating into employee work motivation. This study aims to examine the effect of person job fit, person organization fit and organizational culture on employee performance with work motivation as a mediating variable. The object of this research was BPRS Madina Yogyakarta and BPRS Bangun Drajat Warga Yogyakarta. In this quantitative research, the data were collected through a questionnaire distributed to employees of the two BPRS. The questionnaire involved 65 respondents and was analyzed using the SPSS 23. The results showed a positive influence between person job fit on work motivation, person organization fit had no effect on work motivation, organizational culture had a positive effect on work motivation, work motivation had an effect on positive effect on employee performance, person job fit brought a positive effect on employee performance, person organization fit had no effect on employee performance, and organizational culture had no positive effect on employee performance.